Peningkatan Kemampuan Membaca Lancar Melalui Metode Studi Kasus Melalui Media Cerita Bergambar Pada Siswa Kelas 1 SD - Eli Sofpia; Salsabilla Salsabilla; Chandra Chandra; Ari Suriani (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research was carried out with the aim of improving students' reading skills in Indonesian language subjects using picture story media in class I elementary school at the Al-Marhamah Mosque through a case study method supported by Picture Story media. The subjects were 10 students in class I of Al-Marhamah Mosque Elementary School. Data collection techniques use tests and documentation. The data analysis used is qualitative. The results of the research show an increase in the percentage of reading results, this can be seen from the completion of the KKM or target students from action activities, namely in this study there were 8 students who were fluent in reading. Thus, it can be concluded that the use of picture story media with the help of picture stories in Indonesian language learning can improve students' reading skills even though there are still students who are not yet fluent in reading.